2023
DOI: 10.9734/ajbgmb/2023/v13i2292
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Evaluation of Adult Female Wistar Rats Administered with Ethanolic Extract of Pausinystalia yohimbe Stem Bark

Abstract: Pausinystalia yohimbe (P. yohimbe) stem bark powder is commonly used as seasoning for barbecue beef in Nigeria and some West African countries. This study evaluated the effect of ingesting ethanol extract of P. yohimbe stem bark on some hormones and tissues linked with fertility in female Wistar rats. A total of fifteen adult female Wistar rats weighing between 140 - 160g were used for this study after an initial Acute Toxicity test was done to establish a safe dose range of the extract. The animals were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Group 1 (control) received distilled water (vehicle), Groups 2 and 3 received 400 mg/kg and 800 mg/kg body weight of the ethanol Pausinystalia yohimbe extract respectively via gavages daily for twenty-one ( 21) days. This doses of Pausinystalia yohimbe ethanolic extract given was determined in our previous study [15].…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Group 1 (control) received distilled water (vehicle), Groups 2 and 3 received 400 mg/kg and 800 mg/kg body weight of the ethanol Pausinystalia yohimbe extract respectively via gavages daily for twenty-one ( 21) days. This doses of Pausinystalia yohimbe ethanolic extract given was determined in our previous study [15].…”
Section: Experimental Designmentioning
confidence: 99%
“…Previous research has reported the antifertility effect of Pausinystalia yohimbe in both males and females. Ethanolic and aqueous extracts of Pausinystalia yohimbe were found to disrupt the reproductive system [1,14,15]. These conflicting opinions on the aphrodisiac property of the stem bark have become worrisome especially with the great consumption of the "burantashi" among the populace especially women, young adults, and even children because it greatly attracted public attention and is now a major concern among the populace.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation